The effects of intrinsic foot muscle strengthening interventions for adults over age 65: a randomized controlled trial protocol - Futrell, Erin; Golightly, Yvonne; Haddad, Yara; Carmichael, Andrea; Taylor, David (Frontiers in Aging, 2025)
Unintentional falls are the leading cause of injury in adults ≥65 years. While causes of falls are multifactorial, weakness or disuse of the intrinsic foot muscles (IFM) can contribute. The purpose of this randomized controlled trial, using an effectiveness-implementation hybrid design, is to analyze the effects of two IFM strengthening interventions (minimal footwear use or strengthening exercises) on IFM size, proprioception, foot structure, and fall risk in older adults. Adults ages ≥65 years, with fall risk, who can ambulate household distances (with an assistive device as needed), will be invited to participate. Individuals with poor foot sensation, vestibular disorders, lower extremity amputation, lower extremity or lumbar spine injury or surgery in the previous 6 months, impaired cognitive ability to follow verbal and written instructions, and those who have participated in a fall prevention program in the past 6 months will be excluded. Participants will be randomly allocated into three groups: prescribed minimal footwear use, IFM strengthening exercises, or control. Participants will be encouraged to perform their intervention 5 days per week for 16 weeks, and then at least 2 days per week from 17 weeks to 1 year. Participants will be asked to record intervention performance, daily step count, and falls in provided diaries. At baseline, 8 and 16 weeks, and 1 year, participants will undergo measurements of IFM cross-sectional area (CSA, cm2) using ultrasound imaging, proprioception, foot structure (navicular drop and hallux valgus angle) and fall risk. Semi-structured interviews will be conducted and recorded to gain participant impressions of the interventions, self-reported effects of the interventions, and impressions of study activities to inform future research and clinical implementation. A three-group x four time point repeated measures analysis of covariance will be used to assess changes in measurements. Implementation data will be analyzed using both quantitative and qualitative methods. This will be the first study among older adults to assess the effects of IFM strengthening interventions on long-term fall risk and proprioception, and to use ultrasound imaging to assess IFM size changes. These interventions are simple, safe, and affordable and may have a major impact on functional mobility and reduction of falls for older adults.